Senior design project: test fixture for a lenticular offset composite hinge - Romanowicz, Kaitlyn, author (Colorado State University. Libraries, 2024)
My team and I developed a test method to verify the torque specification of a Lenticular Offset Composite (LOC) hinge. This engineering senior design project was sponsored by Opterus R&D, a company that specializes in deployable spacecraft structures. These hinges are typically mounted in deployable solar array configurations, so research was done to orient to the market demand. A material understanding of the hinge was developed by exploring how high strain composite materials store energy as they deform. After developing this understanding, the previous and current test methods were evaluated to guide my team’s prototype iterations. The final design is a test fixture that improves the user interface when compared to the current method, accommodates a variety of hinge geometries, and mimics the behavior of simulated LOC hinge data. My two main roles throughout the project were to ensure that my team was on track for all deliverables, and machine half of the custom aluminum components for the final product. I gained valuable experience in project management, used many skills that I’ve developed throughout my degree program, and now embody the confidence to start my career as an engineer.
Test fixture for a lenticular offset composite hinge
Test fixture for LOC hinge
Colorado State University. Department of Mechanical Engineering.
Keywords: engineering senior design project; deployable spacecraft structures; high strain composite materials; test methods